Staged stenting strategy of acutely wide-neck ruptured intracranial aneurysms: A meta-analysis and systematic review - Wei, Yanpeng; Zhang, Xiaoxi; Zhang, Renkun; Zhang, Guanghao; Shang, Chenghao; Chen, Rundong; Li, Dan; Huyan, Meihua; Wu, Congyan; Zong, Kang; Feng, Zhengzhe; Dai, Dongwei; et al. (Frontiers in neurology, 2023)
In the study, we explored the safety and effectiveness of staged stenting strategy for acutely wide-neck ruptured intracranial aneurysms. Online databases, including PubMed, EMBASE, the Cochrane database, and Web of Science, were retrospectively and systematically searched. The main observation indicators were the procedure-related complication rate, complete occlusion rate, and favorable clinical outcome. Meta-analysis was performed using a random or fixed effect model based on heterogeneity. A total of 5 studies with 143 patients were included. The hemorrhagic complication rate of the initial coiling and staged stenting was 2.8% (4 of 143) and 0, respectively. The ischemic complication rate of the coiling and supplemental stenting was 3.5% (5 of 143) and 2.9% (4 of 139), respectively. There were no deaths due to procedure-related complications in two stages. The aneurysm complete occlusion rate was 25% (95% CI, 0.13-0.03; I = 4.4%; = 0.168) after initial coiling, 54% (95% CI, 0.63-0.64; I = 0%; = 0.872) after staged stenting, and 74% (95% CI, 0.66-0.81; I = 56.4%; = 0.562) at follow-up, respectively. Favorable clinical outcome rate 74% (95% CI, 0.61-0.86; I = 50.5%; = 0.133) after discharge of initial coiling treatment, and 86% (95% CI, 0.80-0.92; I = 0; = 0.410) after discharge from stenting, and 97% (95% CI, 0.93-1.01; I = 43.8%; = 0.130) at follow-up. Staged stenting treatment of wide-neck RIA with coiling in the acute phase followed by delayed regular stent or flow-diverter stent had high aneurysm occlusion rate, favorable clinical outcome rate and low procedure-related complication rate. A more dedicated and well-designed controlled study is warranted for further evaluation of staged stenting treatment compared to SCA in wide-neck RIA.